Corporate approaches to human sustainability : workforce wellbeing in large Japanese companies : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Management at Massey University, Albany, Auckland, New Zealand - Kobayashi, Kazunori (Massey University, 2019)
Sustainability and Corporate Social Responsibility (CSR) have become widely researched fields. In recent years, there has been a growing social concern about issues affecting workforce wellbeing and human sustainability. However, little is known about how companies resolve these issues. In particular, there is a dearth of empirical research in these fields examining how companies address workforce wellbeing and human sustainability issues under increasing social pressures. To fill this knowledge gap, this exploratory study examines how large Japanese companies address these issues. It is positioned within a social constructionism/interpretivism paradigm and employs qualitative research methodology, drawing upon interviews with managers from 31 companies, as well as their stakeholders and informants. The study begins by examining workforce wellbeing and human sustainability initiatives promoted by large Japanese companies. It identifies four interconnected areas addressed as integral parts of CSR practices: gender equality, flexibility at work, regulating overwork, and productivity improvement. However, while companies promote initiatives under increasing social pressures, they find it difficult to incorporate the initiatives into CSR strategy due to emerging dilemmas. Next, the study explores the business-society interface in which companies face these dilemmas. It identifies nine factors which constrain the implementation of human sustainability initiatives. The evidence indicates that these factors constitute the underlying system of responsibilities that characterises the existing workstyle, leading to externalised overwork and gendered roles in Japanese society. Finally, the study examines how some companies implement human sustainability initiatives as part of their business strategies, even within these constraints. The evidence shows that these companies seek to proactively align core business practices with human sustainability initiatives, in order to enhance business performance over the long run. The findings also suggest that companies seek to proactively engage with key stakeholders to work through existing stakeholders’ expectations. Overall, the outcomes of this thesis elucidate a conceptual framework of the corporate approaches to workforce wellbeing and human sustainability, incorporating the roles of key stakeholders. This may assist scholars and practitioners to address issues affecting workforce wellbeing and human sustainability more effectively within a given social context. Hence, the contributions of this study are both theoretical and empirical.
Keywords: Manpower planning; Personnel management; Employees; Mental health; Diversity in the workplace; Corporate culture; Japan